Explicit Analytic Solution of Vibration Equation for large domain by mean of the Elzaki projected Differential Transform Method - Suleman, Muhammad; Wu, Qingbiao; Elzaki, TM (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The aim of this paper is to present a reliable and efficient algorithm Elzaki projected differential transform method (EPDTM) to obtain the explicit solution of vibration equation for a very large membrane with given initial conditions. By using initial conditions, explicit series solutions for six different cases have been derived for the fast convergence of the solution. Numerical results show the reliability, efficiency and accuracy of Elzaki projected differential transform method (EPDTM). Numerical results for the six different cases are presented graphically.